MAGNITUDE DE EXPRESSÃO E DE CORRELAÇÃO NA PRESENÇA E AUSÊNCIA DE FUNGICIDA EM AVEIA - Bandeira, Taiane P.; Valentini, Ana P. F.; Wagner, Juliano F.; Zambonato, Felipe; Oliveira, Juliana M. d.; Viera, Rogério; Silva, Adair J. d.; Carbonera, Roberto; Berto, Jorge L.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo